Management Accounting in Russia: Problems of Theoretical Study and Practical Application in the Economic Crisis - BOBRYSHEV, Aleksey Nikolaevich; El'CHANINOVA, Ol'ga Viktorovna; TATARINOVA, Maria Nikolaevna; GRISHANOVA, Svetlana Valerievna; FROLOV, Aleksandr Vital'evich (Journal of Advanced Research in Law and Economics, 2017)
The aim of the study is to disclosure laws of management accounting development in Russia and to determine the prospects for further development. The study allowed to produce a multi-dimensional grouping of factors of the genesis of management accounting; to identify the degree of impact of the economic crisis on the formation and development of management accounting (considered ‘the Great Depression (1929-1933).’ The recession of the 1970s, the global financial crisis of 2008); to identify positive and negative effects from the crisis in the economy; as well as the contradictions in the system of accounting and analytical support of firm management in the crisis. In addition the authors characterize the influence of social and cultural environment on the national accounting methodology.